9514 1404 393
Answer:
Step-by-step explanation:
The conjugate is found by changing the sign of the square root term.‡ (For this purpose, i = √-1.)
a) the sign of 3i is changed: 2 + 3i
b) the sign of sqrt(-5) is changed: 8 -sqrt(-5) = 8 -i√5
c) the sign of 2i is changed: 7 +2i
d) the sign of sqrt(7) is changed: 4 +√7
_____
‡ Actually, the conjugate of a binomial is formed by changing the sign <em>between</em> terms. The purpose is to allow the product of the binomial and its conjugate to be the difference of squares.
Conventionally, the conjugate of a complex number is the value with the sign of the imaginary part reversed. That is why (-2i+7)* = 7+2i.
M = 0.025
I hope this helped you.
Answer:
Dom(gof)=Dom(f)={1,3,4}.
(gof)(1)=g{f(1)}=g(2)=3.
(gof)(3)=g{f(3)}=g(5)=1.
(gof)(4)=g{f(4)}=g(1)=3.
∴gof={(1,3),(3,1),(4,3)}.
Answer:
6 dollars
Step-by-step explanation:
Answer:
Step-by-step explanation:
b.
an=an-1+3
C.
when x=15
y=3×15-2=45-2=43
a15=43